PENEGELOLAAN BERBASIS COMMUNITY BASED TOURISM PADA OBJEK WISATA AIR PANAS PAWAN KABUPATEN ROKAN HULU PROVISI RIAU - Ziwista, Berry; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Emphasizes aspects of community-based tourism activities that focus on the community, from the community, by the community for the community.Rokan Hulu has a wide range number of attractions, but which became the excellent potential that is only four; Hot Pawan attractions, Attractions Hot Hapanasan, attractions Lake Sipogas and attractions Waterfall Aek Matua.Attractions hot Pawan a tourist attraction run by the three parties of Regional Government, Rural and Community Government. People who work most management remedy given freedom Attraction manage Hot Pawan by the government through the Department of Culture and Tourism of Rokan Hulu. But does the government involve the community who worked as the manager of the community-based tourism activities as activities Planning, Investor, Implementation, Management and Evaluation